TreEducation A Visual Education Platform for Teaching Treemap Layout Algorithms - Fuchs, Johannes (IEEE transactions on visualization and computer graphics, 2024)
Treemaps are a powerful tool for representing hierarchical data in a space-efficient manner and are used in various domains, including network security or software development. However, interpreting the topology encoded by nested rectangles can be challenging, particularly compared to tree-structured representations like node-link diagrams or icicle plots. To address this challenge, we introduce TreEducation, a visual education platform designed to improve the visualization literacy skills required for reading treemaps among non-expert users. TreEducation is an online application that combines visualizations, interactions, and gamification elements to facilitate understanding of eight different treemap layout algorithms and enhance students' learning process. We evaluated TreEducation in a classroom setting and a controlled environment. Our results indicate a significant knowledge gain of students training exclusively with TreEducation and the usefulness of competition as a social gamification element included in our competitive quiz